Pengaruh Gerak dan Lagu Aku Tresno Yesus Pada Kecerdasan Anak Sekolah Minggu di GBI Apostolic Center Papua: Kajian Interaktif - Prasetya, Didimus Sutanto B.; S, Dewi Lidya (Real Kiddos: Jurnal Pendidikan Anak Usia Dini, 2024)
Improving learning in Sunday school at the GBI Apostolic Center is hampered by limited methods, such as storytelling, question and answer activities, discussions and lectures, as well as limited media and teaching tools such as story books, hand puppets, simple musical instruments and television. Holistic intelligence, namely complete intelligence including intellectual intelligence (IQ), emotional intelligence (EQ), and spiritual intelligence (SQ), is intelligence that every child must have. This intelligence can be stimulated through choreographed movements and songs. This research aims to find and explain the impact of the movement and song Aku Tresno Jesus in stimulating the holistic intelligence of Sunday school children at the GBI Apostolic Center Papua. The research method uses interactive qualitative research with a case study approach. As a result, the use of movement and the song Aku Tresno Jesus can improve children's holistic intelligence. The resulting intellectual intelligence includes kinesthetic, linguistic, musical, intrapersonal and interpersonal. Emotional intelligence is related to children's ability to recognize and manage emotions, enrich their understanding of themselves and others, and foster empathy towards others. The resulting spiritual intelligence is having a relationship and deep love with God.Keywords: Holistic Intelligence; Choreography; Children's SongsAbstrakPeningkatan pembelajaran di sekolah minggu GBI Apostolic Center terkendala pada metode yang terbatas, seperti kegiatan bercerita, tanya jawab, diskusi, dan ceramah, serta keterbatasan media dan alat pengajaran seperti buku cerita, boneka tangan, alat musik sederhana, dan televisi. Kecerdasan holistik yaitu kecerdasan utuh meliputi kecerdasan intelektual (IQ), kecerdasan emosi (EQ), dan kecerdasan spiritual (SQ) merupakan kecerdasan yang harus dimiliki oleh setiap anak. Kecerdasan ini dapat distimulasi melalui koreografi gerak dan lagu. Penelitian ini bertujuan menemukan dan menjelaskan tentang dampak gerak dan lagu Aku Tresno Yesus dalam menstimulasi kecerdasan holistik anak sekolah minggu di GBI Apostolic Center Papua. Metode penelitian menggunakan penelitian kualitatif interaktif dengan pendekatan studi kasus. Hasilnya, penggunaan gerak dan lagu Aku Tresno Yesus dapat meningkatkan kecerdasan holistik anak. Kecerdasan intelektual yang dihasilkan meliputi kinestetik, linguistic, musical, intrapersonal, dan interpersonal. Kecerdasan emosional terkait dengan kemampuan anak mengenali dan mengelola emosi, memperkaya pemahaman diri dan orang lain, serta menumbuhkan empati terhadap sesama. Kecerdasan spiritual yang dihasilkan adalah memiliki hubungan dan adanya kecintaan yang mendalam dengan Tuhan.Kata Kunci: Kecerdasan Holistik; Koreografi; Lagu Anak